Fluorescence to highlight the urethra - a human cadaveric study - Barnes, T; Penna, M; Hompes, R; Cunningham, C (Spinger Verlag, 2017)
Purpose: Urethral injury is a feared complication of surgeons performing transanal TME (TaTME) or abdomino-perineal excision (APE) procedures. Injury during TaTME occurs when the prostate is inadvertently mobilised or as a direct injury similar to the direct injury during the perineal dissection of APE procedures. This is a proof-in-principle study aiming to assess the feasibility of using ICG to fluoresce the urethra in human cadavers. Methods: Indocyanine green at varying doses was mixed with instillagel and infiltrated into the urethra of male human cadavers. The urethra was exposed through either a perineal incision or by mobilisation of the prostate during a TaTME dissection and fluorescence observed using a PINPOINT laparoscope (NOVADAQ). Brightness was assessed on the images using ImageJ (National Institute of Health). Results: Eight cadavers were included in the study. Fluorescence was visualised in the urethra in all 8 cadavers. Minimal dissection was required to obtain fluorescence trans-perineally. In one cadaver the urethra was demonstrated under fluorescence using a simulated TaTME with additional fluorescence also being observed in the prostate. There was no correlation between brightness and dosing. Conclusions: This novel proof of principle study demonstrates a simple way in which the urethra may be easily identified preventing it from injury during surgery.